(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
An analysis was made of 63 literary sources over the past 10 years, of which 16 are Russian-language and 47 are foreign, which reflect the diagnosis and treatment of cavernous malformations (CM) of the brain. When analyzing the literature data, it was revealed that cerebral CMs are the most common vascular malformations and can be found in many places in the brain. Left untreated, cavernomas can lead to intracerebral hemorrhage, seizures, focal neurological disorders, or headaches. The clinical picture and localization of the lesion are the most important factors influencing the determination of the optimal course of treatment for CM.